Changing epidemiology of non-albicans candidemia in Korea. Issue 5 (May 2019) - Ko, Jae-Hoon; Jung, Dong Sik; Lee, Ji Yeon; Kim, Hyun Ah; Ryu, Seong Yeol; Jung, Sook-In; Joo, Eun-Jeong; Cheon, Shinhye; Kim, Yeon-Sook; Kim, Shin-Woo; Cho, Sun Young; Kang, Cheol-In; et al.
Abstract: An epidemiologic surveillance of non- albicans candidemia for a 6-year period was conducted in Korea. Compared to the published epidemiologic data for the previous 6 years, an increase of C. glabrata (from 21.3% to 28.5%) and a decrease of C. parapsilosis (from 36.5% to 24.7%) were noticed. During the study period, C. tropicalis (36.4%) was most frequently isolated non- albicans Candida, followed by C. glabrata (28.5%), C. parapsilosis (24.7%), and C. krusei (2.6%). Replacement of primary amphotericin B treatment with echinocandins ( P  < 0.001) eliminated amphotericin B resistance (from 7.8% in 2011 to 0% in 2014).